Konsekuensi Menolak Ineransi Alkitab - Fajar Kurnia Harefa (Davar : Jurnal Teologi, 2021)
The inerrancy of the Bible relates to the Bible as the Word of God which is free from error in its entirety. The Bible is a life guide for Christians that is useful for teaching, rebuking, correcting behavior and educating people in the truth (2 Tim. 3:16). All his writings were inspired by God to humans (2 Tim. 3:15). However, in the postmodern era, doubts about the innocence of the Bible have resurfaced and been questioned, one of which is about the resurrection of the saints which is considered not to have actually happened (Matt. 27:51-53). Therefore, the focus of this research is to explain what are the theological consequences of rejecting the inerrancy of the Bible and formulate the problem in a question, if the Bible contains errors, then what are the theological consequences? To examine this, this research uses a qualitative method in the realm of systematic theology. The aim is to produce a new study on the consequences of rejecting the inerrancy of the Bible that can provide theoretical benefits, not only as a contribution to research in the field of systematic theology, especially at the Jakarta Sangkakala Theology College, but also to all readers. The results of the research on the consequences of rejecting the inerrancy of the Bible are that first the Bible is not the Word of God because it contains errors, the Bible cannot be believed and the Bible cannot lead to Salvation through Jesus Christ. AbstrakIneransi Alkitab berkaitan dengan Alkitab sebagai Firman Allah yang tidak mengandung kesalahan dalam keseluruhan isinya. Alkitab tersebut merupakan pedoman hidup bagi orang Kristen yang bermanfaat untuk mengajar, menyatakan kesalahan, memperbaiki kelakuan dan mendidik orang dalam kebenaran (2 Tim. 3:16). Adapun segala tulisannya diilhamkan Allah kepada manusia (2 Tim. 3:15). Akan tetapi, di era postmodern, keraguan akan ketidakbersalahan Alkitab mencuat kembali dan dipertanyakan, dimana salah satunya adalah mengenai kebangkitan orang-orang kudus yang dianggap tidak benar-benar terjadi (Mat. 27:51-53). Karena itu, fokus penelitian ini adalah menjelaskan apa saja konsekuensi teologis menolak ineransi Alkitab dan merumuskan masalahnya pada sebuah pertanyaan, jika Alkitab mengandung kesalahan, lalu apa konsekuensi teologisnya? Untuk meneliti hal tersebut penelitian ini menggunakan metode Kualitatif dalam ranah teologi sistematika. Tujuannya yaitu menghasilkan sebuah kajian baru terhadap konsekuensi menolak Ineransi Alkitab yang dapat memberikan manfaat teoritis, tidak hanya sebagai kontribusi dalam penelitian bidang teologi sistematika, khususnya di Sekolah Tinggi Teologi Sangkakala Jakarta, namun juga kepada seluruh pembaca. Adapun hasil dari penelitian konsekuensi menolak ineransi Alkitab adalah yang pertama Alkitab bukanlah Firman Allah karena mengandung kesalahan, Alkitab tidak dapat di Imani dan Alkitab tidak dapat menuntun kepada Keselamatan melalui Yesus Kristus.